Evaluating the Concordance of Clinician Antiretroviral Prescribing Practices and HIV-ASSIST, an Online Clinical Decision Support Tool - Ramirez, Jesus A. (J Gen Intern Med, 2019)
BACKGROUND: Individualized selection of antiretroviral (ARV) therapy is complex, considering drug resistance, comorbidities, drug-drug interactions, and other factors. HIV-ASSIST (www.hivassist.com) is a free, online tool that provides ARV decision support. HIV-ASSIST synthesizes patient and virus-specific attributes to rank ARV combinations based upon a composite objective of achieving viral suppression and maximizing tolerability. OBJECTIVE: To evaluate concordance of HIV-ASSIST recommendations with ARV selections of experienced HIV clinicians. DESIGN: Retrospective cohort study. PATIENTS: New and established patients at the Johns Hopkins Bartlett HIV Clinic and San Francisco Veterans Affairs HIV Clinic completing clinic visits were included. Chart reviews were conducted of the most recent clinic visit to generate HIV-ASSIST recommendations, which were compared to prescribed regimens. MAIN MEASURES: For each provider-prescribed regimen, we assessed its corresponding HIV-ASSIST “weighted score” (scale of 0 to 10 +, scores of < 2.0 are preferred), rank within HIV-ASSIST’s ordered listing of ARV regimens, and concordance with the top five HIV-ASSIST ranked outputs. KEY RESULTS: Among 106 patients (16% female), 23 (22%) were ARV-naïve. HIV-ASSIST outputs for ARV-naïve patients were 100% concordant with prescribed regimens (median rank 1 [IQR 1–3], median weighted score 1.1 [IQR 1–1.2]). For 18 (17%) ARV-experienced patients with ongoing viremia, HIV-ASSIST outputs were 89% concordant with prescribed regimens (median rank 2 [IQR 1–3], median weighted score 1 [IQR 1–1.2]). For 65 (61.3%) patients that were suppressed on a current ARV regimen, HIV-ASSIST recommendations were concordant 88% of the time (median rank 1 [IQR 1–1], median weighted score 1.1 [IQR 1–1.6]). In 18% of cases, HIV-ASSIST weighted score suggested that the prescribed regimen would be considered “less preferred” (score > 2.0) than other available alternatives. CONCLUSION: HIV-ASSIST is an educational decision support tool that provides ARV recommendations concordant with experienced HIV providers from two major academic centers for a diverse set of patient scenarios. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05531-4) contains supplementary material, which is available to authorized users.